International Variations in Peritoneal Dialysis Utilization and Implications for Practice - Briggs, Victoria; Davies, Simon; Wilkie, Martin (American journal of kidney diseases, 2019)
In many countries, the use of peritoneal dialysis (PD) remains low despite arguments that support its greater use, including dialysis treatment away from hospital settings, avoidance of central venous catheters, and potential health economic advantages. Training patients to manage aspects of their own care has the potential to enhance health literacy and increase patient involvement, independence, quality of life, and cost-effectiveness of care. Complex reasons underlie the variable use of PD across the world, acting at the level of the patient, the health care team that is responsible for them, and the health care system that they find themselves in. Important among these is the availability of competitively priced dialysis fluid. A number of key interventions can affect the uptake of PD. These include high-quality patient education around dialysis modality choice, timely and successful catheter placement, satisfactory patient training, and continued support that is tailored for specific needs, for example, when people present late requiring dialysis. Several health system changes have been shown to increase PD use, such as targeted funding, PD First initiatives, or physician-inserted PD catheters. This review explores the factors that explain the considerable international variation in the use of PD and presents interventions that can potentially affect them.